Barriers to, and enablers of urban tree planting in low-cost housing areas: lessons from participatory learning processes in South Africa - Gwedla, Nanamhla (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
The recent pronouncement of low-cost housing areas as sustainable human settlements came with an expectation for their development in line with Sustainable Development Goal (SDG) 11. Unfortunately, the historical legacy and various socio-economic, socio-political, and socio-cultural dynamics characteristic of these areas have proven it challenging for them to conform to all requirements of urban sustainability, as evidenced in part by the virtual lack of greenspaces and urban trees. Through a three-tier inquiry of urban tree planting in low-cost housing areas using inductive and deductive mixed methods approaches, the aim of this research was to investigate the barriers to, and enablers of, tree planting in low-cost housing areas, and explore participatory learning opportunities to address the challenges and enhance the enablers. In the first segment, a participatory urban forest governance conceptual framing lens was used to situate the various actors in the development of the low-cost housing area urban forest and the dynamics of their involvement in that regard. Inquiry focused on an overview of tree planting across South Africa using key informant interviews, observations and document analysis. Secondly, distribution of trees, and barriers and enablers of tree planting in selected low-cost housing areas in the Eastern Cape province using household surveys, observations, key informant interviews and document analysis were investigated. Finally, drawing on interventionist methodology and adoption of Cultural-Historical Activity Theory (CHAT), the third segment tested scenarios of tree planting in three different small towns through focus group discussions and knowledge-sharing awareness events about trees and tree planting using an activity systems approach. Findings from the first segment ascertain the national Department of Environment, Forestry and Fisheries (DEFF) as the custodian of forestry, and by extension urban forestry in South Africa. Municipalities are tasked with implementing greening plans and strategies for public space planting, while private businesses collaborate with entities to contribute to tree-planting as part of their Corporate Social Responsibility (CSR). Civil society, including residents and Non-Governmental Organizations (NGOs) also contribute, especially for private space planting. However, there are currently very few initiatives implemented in low-cost housing areas. An assessment of ten tree planting initiatives revealed that the DEFF is the most common partner and stakeholder, and normally provides resources such as funding and trees. Most programs reported having undertaken community engagement before and during the tree planting. The general outcomes of these initiatives were centred on the survival rate of trees, job creation, and development of parks and gardens. Findings from the first part of the second segment, conducted in eight small-medium sized towns in the Eastern Cape, revealed a general lack of trees along streets of both the newly developed and old low-cost housing areas. In the private spaces, most households (52 %) reported having at least one tree in their yard, with households in the older suburbs (60 %) reporting more trees than the newer ones (44 %). Most of these trees (66 %) had been planted as opposed to natural regeneration. Previous participation in urban tree planting programs was low, but 75 % of residents expressed willingness to participate in the future. Municipal officials from these towns corroborated that they do not host tree planting events or initiatives, which was demonstrated by the limited incorporation of urban forestry and urban greening in municipal Integrated Development Plans (IDP). In the second part of the second segment, three groupings of barriers and enablers into biophysical, social, and resources revealed that the most mentioned barriers for the private space were resource barriers. The most prominent barriers were limited space in people's yards, insufficient funds for tree purchases and associated resources, the lack of equipment, and damage to planted trees. Private space enablers of tree planting suggested include the availability of funds, allocation of space, and changes in attitudes towards trees. According to residents, the most prominent barriers to public space planting include the perceived incompetence of municipalities, limited space on the street, insufficient funds for tree planting programmes, damage to trees in public spaces, crime associated with street trees, and politics. Additionally, municipal officials reported that their efforts to plant trees were hindered by lack of communication and coordination between municipal departments. Residents suggested that enlisting the skills of residents for tree planting, engaging in education and awareness initiatives about trees and tree planting, and changing attitudes towards trees could enable tree planting. Municipal officials opined that education and awareness, revisions to and implementation of Environmental Management Plans, and inter-departmental collaborations and partnerships could improve the prospects for public space planting. Drawing on key findings from the second segment, an intervention to involve communities in tree planting using a case study approach in three towns ensued. Here an activity systems analysis of participatory tree planting initiatives was used. Findings revealed an array of multi-activity systems with multiple and partially overlapping objectives related to tree planting. Residents demonstrated that, with support, they can champion urban tree planting for their suburbs. However, contradictions and tensions within and between various activity systems emerged, creating opportunities for the expansive transformation of an activity that was previously not a priority. This study highlights the current distribution of power and resources in the governance system of the urban forest, ascertains the spatial heterogeneity of urban trees in areas of a similar socio-economic context, and provides lessons for best-practice in tree planting that involves multiple actors. It provides in-depth insights into what constrains tree planting, and highlights the importance of residents in the governance system of urban forests and how this can constrain or advance tree planting. Further research in participatory urban forest governance for a developing country, low-income context could utilize an expansive learning platform as this will provide first-hand experiences into learning what is not yet there, and provide communities with the opportunities to explore and devise localized solutions to the lack of trees in their residential areas.
Keywords: Urban ecology (Sociology) -- South Africa -- Eastern Cape; Tree planting -- South Africa -- Eastern Cape; Trees in cities -- South Africa -- Eastern Cape; Urban forestry -- Law and legislation -- South Africa -- Eastern Cape; Low-income housing -- South Africa -- Eastern Cape; Cultural Historical Activity Theory (CHAT)